Enhancing employee retention in the UAE oil and gas sector: The role of training, intrinsic motivation, and job satisfaction - Akmal, Suriati; Alswaidi, Khaled Essay (Human Resource Management Academic Research Society, 2024)
In today's business environment, effectively managing human resources is crucial for boosting productivity and optimizing resource use. Employee retention is a major concern, especially in the UAE’s Oil and Gas sector, where high turnover rates are prevalent. Research highlights that employee satisfaction, significantly influenced by training, is essential for improving retention. Training enhances employees' skills and knowledge, fostering greater commitment and dedication. Tailoring training programs to specific needs is vital for increasing employee engagement and retention. Despite this, there is limited empirical research on how training development impacts employee retention in the UAE’s oil sector. Therefore, this study aims to examine the relationship between training and development and employees’ intrinsic motivation and satisfaction and consequently influence employees’ retention. Based on a survey of 321 ADNOC employees, the research finds that training and development positively influence employee retention and intrinsic motivation. Intrinsic motivation and job satisfaction also positively affect retention. These insights contribute to understanding how aligning training and development with the Psychological Contract can effectively enhance employee retention in the UAE's oil and gas industry.